Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
FH =KH if triangle FJH and KJH is congruent
Step-by-step explanation:
If two triangles FJH and KJH as shown n figure is congruent if,
FJ = KJ,
FH =KH and
JH =JH common
Triangle is congruent by SSS theorem
Therefore FH =KH
![View image DerrickStalvey](https://us-static.z-dn.net/files/dd1/cfcdc7bbfa1511d7673cf08e3fc4b0a9.png)
Answer:
FH=39
Step-by-step explanation:
FGH~KJH
GH=x+8
FH=4x-25
JH=32
KH=52
(these are the measurements I have)
x+8 / 32 = 4x-25 / 52
(cross multiply)
52(x+8) = 32(4x-25)
52x+416 = 128x-800
(subtract the 52x from the 128x)
416 = 76x-800
(add the 800 to the 416)
1216 = 76x
(divide the 76 over the 1216)
x = 16
(now plug x into FH)
FH = 4x-25
FH = 4(16)-25
FH = 39
(hope this helped)
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.